Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```        if ƒ:R→R be defined by ƒ(x) : x2+1 , then find ƒ-1(17) and ƒ-1(-3).

The answer is given as :
ƒ-1(17) = {-4,4} , ƒ-1(-3) = ø```
6 years ago

mayur hampiholi
16 Points
```										BASICALLY U NEED TO KNW THE VERY BASIC DEF OF INVERSE FN..
IF
Y=F(X)
X=F-1(Y)
NEEDLESS TO SAY THAT FOR AN EXAMPLE:
LEY Y=2*X                    X=3 => Y=6
SO, F-1(6)=3
UNDERSTOOD????
NOW F(X)=X^2+1
F-1(17)=X     =>F(X)=17
SO X^22+1=17
SO X=+4 OR -4
SIMILARLY..........
X2+1=-3
=>X2=-4
NOT POSSIBLE
```
6 years ago
510 Points
```										f(x) = x2 + 1
f(x) = y
x = f-1(y)        .....................1
y = x2 + 1
(y-1)1/2 = x     ..............2
from eq 1
f-1(y) = (y-1)1/2
so , f-1(x) = (x-1)1/2            ,      {  for all x > = 1 }

f-117 = +(-)4 = {-4,4}
f-1-3 = @ , coz x cannot take any value less than 1 ...
```
6 years ago
Neer Varshney
76 Points
```										f(x)= x2 + 1
f(1/x)= 1/(x2+1)
f-1(x)= 1/(x2+1)
f-1(17)= 1/(x2+1)
1/17 = 1/x2+1
17= x2 + 1
x2 = 16
x= {+4.-4}

Similarly for -3
x2 + 1 = -3
x2  = -4
x= under root -4
imaginary no.
hence f-1(-3) = 0.

plz approve....
```
6 years ago
amit karn
21 Points
```										let  y= x2 + 1
=> x2 = y-1
=> x =  √y-1
then replace y by x we get,
f-1 (x) = √x-1
then put the value of x.
```
6 years ago
Sudheesh Singanamalla
114 Points
```										Thanks a lot
```
6 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Magical Mathematics[Interesting Approach]

View all Questions »
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details
Get extra Rs. 3,180 off
USE CODE: CHEM20
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details
Get extra Rs. 3,180 off
USE CODE: CHEM20